PENGARUH PELATIHAN DAN BUDAYA ORGANISASI TERHADAP EFEKTIFITAS KINERJA KARYAWAN - Fatihin, Amirul; Rokhman, Wahibur (EQUILIBRIUM, 2014)
The current study explored the relationship between training, organizational culture, and work performance in Islamic microfinance institutions in Kudus Regency. Specifically, this study examined the effect of training and organizational culture on performance among employees. Survey data was consisted of 84 employees from Islamic microfinance institutions. The empirical tests indicated that training has significant effect on performance. Also, organizational culture has significant effect on performance. Implication, limitation and suggestion for future research are discussed.Keywords:   training, organizational culturePenelitian ini menguji hubungan antara pelatihan, budaya organisasi dan kinerja di lembaga keuangan mikro syariah di Kabupaten Kudus. Penelitian ini menguji pengaruh pelatihan dan budaya organisasi terhadap kinerja karyawan. Sampel penelitian ini sebnyak 84 karyawan dari lembaga keuangan mikro syariah. Hasil penelitian ini menunjukkan bahwa pelatihan berpengaruh signifikan terhadap kinerja. Lebih lanjut, budaya organisasi berpengaruh signifikan terhadap kinerja.Kata kunci: Pelatihan, Budaya organisasi serta efektifitas dan kinerja